Survival after lumpectomy and mastectomy for early stage invasive breast cancer. Issue 7 (28th January 2013) - Hwang, E. Shelley; Lichtensztajn, Daphne Y.; Gomez, Scarlett Lin; Fowble, Barbara; Clarke, Christina A.
Abstract BACKGROUND: Randomized clinical trials (RCT) have demonstrated equivalent survival for breast‐conserving therapy with radiation (BCT) and mastectomy for early‐stage breast cancer. A large, population‐based series of women who underwent BCT or mastectomy was studied to observe whether outcomes of RCT were achieved in the general population, and whether survival differed by surgery type when stratified by age and hormone receptor (HR) status. METHODS: Information was obtained regarding all women diagnosed in the state of California with stage I or II breast cancer between 1990 and 2004, who were treated with either BCT or mastectomy and followed for vital status through December 2009. Cox proportional hazards modeling was used to compare overall survival (OS) and disease‐specific survival (DSS) between BCT and mastectomy groups. Analyses were stratified by age group (< 50 years and ≥ 50 years) and tumor HR status. RESULTS: A total of 112, 154 women fulfilled eligibility criteria. Women undergoing BCT had improved OS and DSS compared with women with mastectomy (adjusted hazard ratio for OS entire cohort = 0.81, 95% confidence interval [CI] = 0.80‐0.83). The DSS benefit with BCT compared with mastectomy was greater among women age ≥ 50 with HR‐positive disease (hazard ratio = 0.86, 95% CI = 0.82‐0.91) than among women age < 50 with HR‐negative disease (hazard ratio = 0.88, 95% CI = 0.79‐0.98); however, this trend was seen among all subgroups analyzed. CONCLUSIONS: Among patients with early stage breast cancer, BCT was associated with improved DSS. These data provide confidence that BCT remains an effective alternative to mastectomy for early stage disease regardless of age or HR status. Cancer 2013. © 2012 American Cancer Society.